Computer networking : - Kurose, James K. (Pearson, 2013)
Building on the successful top-down approach of previous editions, the Sixth Edition of Computer Networking continues with an early emphasis on application-layer paradigms and application programming interfaces (the top layer), encouraging a hands-on experience with protocols and networking concepts, before working down the protocol stack to more abstract layers.